Implementation of Compensation for Oil Pollution by Tanker Ships in the Indonesian Legal System - Purwendah, Elly Kristiani; Mangku, Dewa Gede Sudika (International Journal of Criminology and Sociology, 2021)
The government needs to restructure the institutions that are responsible for prosecution and the calculation of appropriate compensation to avoid the time-consuming and complicated process of calculating losses and need to establish a loss adjuster agency. The Coordinating Ministry for Maritime Affairs is expected to be the coordinator, coordinating other agencies based on a marine data base and a method of calculating compensation for all existing resources. It is necessary to create a special procedural law system for environmental compensation considering the application of the precautionary principle, the polluter pays principle and strict liability in cases of tanker oil pollution which have special characteristics given the civil responsibility and liability for Protection & Indemnity (P&I) insurance.